Redistribution of a major cell surface glycoprotein during cell movement (The Rockefeller University Press, 1984)
The distribution in living cells of an 80,000-dalton major cell surface glycoprotein of murine fibroblasts has been studied by use of monoclonal antibodies. The presence of the molecule throughout the plasma membrane and on the substrate attached surface of the cell was demonstrated by immunofluorescence. Cell growth kinetics were not altered and the cells remained motile in the presence of the antibody. The uniform distribution of the direct immunofluorescence stain persisted for long periods (greater than 100 h), which indicates that the fluorescent monoclonal antibodies may be used to trace antigen surface distribution during cell functions. In motile cells, but not G0 or confluent cells, the degree of fluorescent staining decreased toward the leading edge; this gradient increased markedly during the time that the antibody was bound to the cells. However, the gradation was not seen with the lipid probe, dihexadecylindocarbocyanine. The antigen was "patched" only by the application of a second antibody directed to the rat monoclonal antibody and the relationships of these patches to the underlying cytoskeleton were characterized.